(untitled) (World Bulletin of Management and Law, 2023)
This article analyzes the use of gijzeling as an instrument for tax law enforcement in Indonesia, focusing on the context of its implementation, psychological impact, and the effect of compliance on tax debt. Within the framework of Law Number 19 of 2000 concerning Collection of Taxes by Forced Letter (UU PPSP), gijzeling is enacted as the last step to encourage taxpayers or guarantor taxes settle tax debts. The analysis underlines that the criminal sanctions stipulated in Article 41 A of the PPSP Law put significant financial pressure as well as psychological pressure on taxpayers or guarantor tax . The threat or execution of gijzeling has the potential to motivate the payment of tax debts quickly in order to avoid criminal risks and fines. In addition, this study reviews the legal provisions governing gijzeling , considering aspects of human rights and legal protection for taxpayers . or guarantor tax . The results of the analysis show that gijzeling is not only a financial collection tool, but also has psychological implications that can encourage compliance with tax obligations. This research provides an indepth look at the effectiveness and impact of gijzeling in encouraging the payment of tax debts, and emphasizes the importance of a balance between law enforcement and individual human rights in the context of tax collection in Indonesia.